2015
DOI: 10.4028/www.scientific.net/msf.815.503
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermomechanical Properties of Nylon6T/66/PPS Blends

Abstract: Polymer blending is a very important and widely used method for the modification of polymer materials. However, little attention has been paid to the Semi-aromatic Polyamides with PPS blends. In this article, we investigate the properties of Poly (phenylene sulfide) (PPS) blends with Poly (hexamethylene terephthalamide/hexamethylene hexanediamide) (nylon 6T/66). The structure, mechanical properties of nylon 6T/66 and (PPS) blends were studied by scanning electron microscopy (SEM), Differential scanning calorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Semiaromatic polyamides such as PA6T and PA6I, derived from 1,6-HDA with terephthalic or isophthalic acid, respectively, are heat resistant polymers with high melting and glass-transition temperatures, high rigidity, and low water absorption. 1350 Recent work by Shen et al synthesized PA5F and PA10F, novel semi-aromatic polyamides of 2,5-FDCA with 1,5-PeDA and 1,10-decanediamine, respectively. 1351 Both polyamides showed high thermal stability (i.e., up to 380 °C), with PA5F showing a relatively high T g of 86 °C and PA10F exhibiting a lower T g of 35 °C, and were identified by the authors as potentially useful materials for bio-based 3D-printing applications.…”
Section: Polyamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Semiaromatic polyamides such as PA6T and PA6I, derived from 1,6-HDA with terephthalic or isophthalic acid, respectively, are heat resistant polymers with high melting and glass-transition temperatures, high rigidity, and low water absorption. 1350 Recent work by Shen et al synthesized PA5F and PA10F, novel semi-aromatic polyamides of 2,5-FDCA with 1,5-PeDA and 1,10-decanediamine, respectively. 1351 Both polyamides showed high thermal stability (i.e., up to 380 °C), with PA5F showing a relatively high T g of 86 °C and PA10F exhibiting a lower T g of 35 °C, and were identified by the authors as potentially useful materials for bio-based 3D-printing applications.…”
Section: Polyamidesmentioning
confidence: 99%
“…Partially or fully aromatic polyamides, termed aramids if >85% of the amide linkages are between two aromatic rings, are very high-performance polyamides, with aerospace and military applications such as Kevlar for bulletproof vests. Semi-aromatic polyamides such as PA6T and PA6I, derived from 1,6-HDA with terephthalic or isophthalic acid, respectively, are heat resistant polymers with high melting and glass-transition temperatures, high rigidity, and low water absorption . Recent work by Shen et al .…”
Section: Bisfunctional Monomers Used In the Synthesis Of Commodity Th...mentioning
confidence: 99%
“…21 For combining the properties of various polymers, copolymerization or blending method is generally used. [22][23][24] For example, Wang et al synthesized PA6T/6 (50:50) copolymers with high content of the rigid aromatic units, which shows improved thermal stability and mechanical properties. 25 Qu et al obtained PA6T/2T copolymer and found the melting temperature decreased from 368 o C for PA6T to 347 o C for PA6T/2T copolymer.…”
Section: Introductionmentioning
confidence: 99%